Associations between Zinc and Hemoglobin Concentrations in Preschool Children and Women of Reproductive Age: An Analysis of Representative Survey Data from the Biomarkers Reflecting Inflammation and Nutritional Determinants of Anemia (BRINDA) Project. Issue 5 (9th March 2021) - Greffeuille, Valerie; Fortin, Sonia; Gibson, Rosalind; Rohner, Fabian; Williams, Anne; Young, Melissa F; Houghton, Lisa; Ou, Jiangda; Dijkhuizen, Marjoleine A; Wirth, James P; Lander, Rebecca L; McDonald, Christine M; et al.
ABSTRACT: Background: Anemia is a worldwide concern. Nutritional deficiencies and inflammation are considered main contributors, but zinc deficiency has only recently been associated with anemia. Objectives: In this study we assessed associations between zinc status and hemoglobin (Hb) concentrations and anemia in preschool children 6–59 mo old (PSC) and nonpregnant women of reproductive age 15–49 y old (WRA) in population-based nutrition surveys. Methods: Cross-sectional data from 13 (PSC) and 12 (WRA) countries within the Biomarkers Reflecting Inflammation and Nutritional Determinants of Anemia (BRINDA) project were used. Multivariable linear models were constructed that included zinc status (plasma/serum zinc concentrations), Hb concentrations and anemia, iron status, age, sex, and inflammation (C-reactive protein and α-1-acid glycoprotein). Zinc was adjusted for inflammation in PSC according to the BRINDA algorithm. Results: Data were available for 18, 658 PSC and 22, 633 WRA. Prevalence of anemia ranged from 7.5% to 73.7% and from 11.5% to 94.7% in PSC and WRA, respectively. Prevalence of zinc deficiency ranged from 9.2% to 78.4% in PSC and from 9.8% to 84.7% in WRA, with prevalence of zinc deficiency >20% in all countries except Azerbaijan (PSC), Ecuador (PSC), and the United Kingdom (WRA). Multivariable linear regression models showed that zinc concentrations were independently and positively associated with Hb concentrations in 7 of 13 countries for PSC and 5 of 12 countries for WRA. In the same models, ferritin concentration was also significantly associated with Hb among PSC and WRA in 9 and 10 countries, respectively. Zinc deficiency was significantly associated with anemia in PSC and WRA in 5 and 4 countries respectively. Conclusions: Zinc deficiency was prevalent in most countries and associations between zinc and Hb in roughly half of the countries examined suggesting that strategies to combat zinc deficiency may help reduce anemia prevalence. More research on mechanisms by which zinc deficiency is associated with anemia and the reasons for the heterogeneity among countries is warranted.